Polycyclic Aromatic Hydrocarbons identification and source discrimination in rural soil of the northern Persian Gulf coast - Valizadeh-Kakhki, Fatemeh; Zakaria, Mohamad Pauzi; Aris, Ahmad Zaharin; Zulkifli, Syaizwan Zahmir; Mohammadi, Mehdi; Tajik, Hasan (Thai Society of Higher Education, 2014)
Due to strategic situation of the Persian Gulf, identifying the petroleum pollution level and source is an important issue. Therefore, this paper enhanced fingerprinting method of applying biomarkers Polycyclic Aromatic Hydrocarbons (PAHs) in identifying source and distribution of oil spills of the exposed areas. 10 soil samples collected from the northern coasts of the Persian Gulf along three provinces in the south of Iran. PAH concentrations in the soil ranged from 42.76 to 5596.49 ng.g-1. In the present study the distribution of 3 ringed PAHs was much higher than the other PAHs. Phenanthrene and alkylated derivatives of phenanthrene such as 3-methyl, 2-methyl, 9-methyl and 1-methyl phenanthrene were distinctively higher than the other components. According to the result PAHs concentration can be considered as no or little risk of toxicity for the organisms living in soil except for Fluoranthhene, comparing LD50. Applying marker ratios revealed that in most of the sampling sites showed perogenic sources and it emphasizes on the direct impact of oil and petroleum products to the lands due to oil well exploitation and transferring pipelines.